Prevalence and academic impact of allergic rhinitis among school-age children in rural Bengaluru: a cross-sectional study - H. M., Saritha; Govindaraj, Raghul; Kumaraswamy , Nagarathna Hosalli (International Journal of Contemporary Pediatrics, 2026)
Background: Allergic rhinitis (AR) is a prevalent, but often an underdiagnosed, chronic condition in children, which may have a negative impact on quality of life (QoL) and academic performance. Objectives were to determine the prevalence of AR in Indian school children using the score for AR (SFAR), its impact on QoL using the mini-rhino conjunctivitis QoL questionnaire (Mini-RQLQ), and to assess its effect on studies. Methods: A descriptive cross-sectional study was conducted among 300 school children (6th-12th grades) in rural Bengaluru from June to August 2025 using parent-assisted SFAR, mini-RQLQ, and academic impact structured questionnaires. Statistical analyses were conducted in SPSS v25. Associations were tested using Chi-square and ANOVA, with p<0.05 considered significant. Results: AR (SFAR≥7) was found in 55 children (18.3%) with prime triggers being cold weather (68%) and house dust (63%). Children with AR experienced sleeper disturbance, fatigue and ocular symptoms at higher rates. AR was significantly associated with impaired concentration (68.5%), reduced class participation (64.3%), and poorer examination performance (70%) compared to non-AR peers (p<0.001 for all). Nearly 40% of affected kids had doctor visit. Conclusions: AR is common in school children of rural Bangalore and causes considerable impact to QoL and academic performance. Regular screening and timely intervention may help to reduce educational and psychosocial impacts.